2017
DOI: 10.1080/13621718.2016.1240980
|View full text |Cite
|
Sign up to set email alerts
|

High resolution imaging of martensitic all-weld metal

Abstract: Martensitic steel welds show promising results regarding their strength while they may tend to be brittle. As martensite is a quite complex microstructure, high resolution techniques like electron backscatter diffraction (EBSD) and atom probe tomography (APT) are valuable tools for an in-depth characterisation. In this study, the average block size and misorientation distribution of martensitic all-weld samples were evaluated with EBSD. A lower carbon content led to a smaller block size and consequently a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…10 nA. Other scan parameters can be found in [13]. The EBSD scans were performed on cross-sections of the welds and covered a large area (magnification from 3009 to 8009) to maximize statistics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 nA. Other scan parameters can be found in [13]. The EBSD scans were performed on cross-sections of the welds and covered a large area (magnification from 3009 to 8009) to maximize statistics.…”
Section: Methodsmentioning
confidence: 99%
“…However, the desired strength level for the consumable in the current paper requires a fully martensitic microstructure also in the weld metal. A proper way to characterize martensitic all-weld metal was reported in [13] and [14]. The strength and toughness of martensite and the most probable crack propagation paths have been discussed intensely in the last few years by interpreting electron backscatter diffraction (EBSD) results and fracture surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that steels' welding relies on the optimum size and number density of nonmetallic inclusions as a potent heterogeneous nucleation site, which promotes acicular ferrite (AF) formation [13][14][15]. The best impact toughness in steels is achieved through AF due to the high angle grain boundaries (HAGB) density and chaotic ne interlocking sheaves microstructure [16][17][18]. Mabucci et al [19] showed that manganese depletion in the ferrite matrix-manganese sul de interface is associated with manganese precipitates' formation on the oxide inclusions during cooling; this is one of the critical mechanisms of AF formation.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, experiments are running with the goal of developing a filler material with a yield strength of 1100 MPa. Several alloying systems were used in previous studies, leading to promising results regarding both strength and toughness [8,9]. In these studies, high-resolution imaging methods were applied to analyze the microstructure of the welds [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several alloying systems were used in previous studies, leading to promising results regarding both strength and toughness [8,9]. In these studies, high-resolution imaging methods were applied to analyze the microstructure of the welds [9]. It was shown that microalloying can serve as an alternative concept for welds regarding strengthening [8].…”
Section: Introductionmentioning
confidence: 99%